2020
DOI: 10.1055/s-0040-1710501
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhage Risk Assessment on Admission: Utility for Prediction of Maternal Morbidity

Abstract: Objective Hemorrhage is a major cause of maternal morbidity and mortality prompting creation of innovative risk assessment tools to identify patients at highest risk. We aimed to investigate the association of hemorrhage risk assessment with maternal morbidity and to evaluate maternal outcomes after implementation of the risk assessment across hospital sites. Study Design We conducted a retrospective cohort analysis of a multicenter database including women admitted to labor and delivery from Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
4
9
0
3
Order By: Relevance
“…Utilization of the hemorrhage risk score not only predicts the occurrence of hemorrhage, but also the occurrence of hemorrhage-associated morbidity such as transfusion, hysterectomy, or coagulopathy. 14 Similar to previous work, we found that patients who were scored as medium or high risk for hemorrhage had significantly higher odds of receiving a transfusion compared with lowrisk patients. 14,16,23 Using the CDC criteria for SMM, transfusion has been documented as the most prevalent indicator for SMM.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Utilization of the hemorrhage risk score not only predicts the occurrence of hemorrhage, but also the occurrence of hemorrhage-associated morbidity such as transfusion, hysterectomy, or coagulopathy. 14 Similar to previous work, we found that patients who were scored as medium or high risk for hemorrhage had significantly higher odds of receiving a transfusion compared with lowrisk patients. 14,16,23 Using the CDC criteria for SMM, transfusion has been documented as the most prevalent indicator for SMM.…”
Section: Resultssupporting
confidence: 89%
“…14 Similar to previous work, we found that patients who were scored as medium or high risk for hemorrhage had significantly higher odds of receiving a transfusion compared with lowrisk patients. 14,16,23 Using the CDC criteria for SMM, transfusion has been documented as the most prevalent indicator for SMM. 4,18 As expected, transfusion was a driving factor for the association of hemorrhage risk score with SMM in our study.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Although the hemorrhage risk prediction tools differed, thus leading to differences in categorization of patients with similar characteristics, both achieved the same outcome, the ability to differentiate risk. Both tools have similar predictive capability and are similar to prior predictive analysis on the Association of Women's Health, Obstetric and Neonatal Nurses (AWHONN) hemorrhage risk prediction tool completed by Ahmadzia et al 8 Importantly, these tools are able to discriminate risk threshold but have poor PPV and sensitivity. 8 Additionally, a significant proportion of OBHs occurred in women classified as low risk, highlighting an opportunity to enhance existing hemorrhage risk prediction tools.…”
Section: Discussionmentioning
confidence: 77%
“…It was designed as a risk-stratification method, identifying patients with low, medium, or high risk for obstetric hemorrhage 29 . Prior studies have suggested that this tool works moderately well to identify patients at highest risk for both obstetric hemorrhage and transfusion 17 , and when implemented, may reduce rates of maternal morbidity 33 . Our study demonstrates that, in addition to predicting obstetric hemorrhage, the AWHONN risk assessment tool identifies women at highest risk for hemorrhage-related morbidity, which may be more clinically relevant.…”
Section: Discussionmentioning
confidence: 99%